Partial loss of psychiatric risk gene Mir137 in mice causes repetitive behavior and impairs sociability and learning via increased Pde10a. (December 2018) - Cheng, Ying; Wang, Zhi-Meng; Tan, Weiqi; Wang, Xiaona; Li, Yujing; Bai, Bing; Li, Yuxin; Zhang, Shuang-Feng; Yan, Hai-Liang; Chen, Zuo-Lun; Liu, Chang-Mei; Mi, Ting-Wei; et al.
Abstract Genetic analyses have linked microRNA-137 (MIR137) to neuropsychiatric disorders, including schizophrenia and autism spectrum disorder. miR-137 plays important roles in neurogenesis and neuronal maturation, but the impact of miR-137 loss-of-function in vivo remains unclear. Here we show the complete loss of miR-137 in the mouse germline knockout or nervous system knockout (cKO) leads to postnatal lethality, while heterozygous germline knockout and cKO mice remain viable. Partial loss of miR-137 in heterozygous cKO mice results in dysregulated synaptic plasticity, repetitive behavior, and impaired learning and social behavior. Transcriptomic and proteomic analyses revealed that the miR-137 mRNA target, phosphodiesterase 10a (Pde10a), is elevated in heterozygous knockout mice. Treatment with the Pde10a inhibitor papaverine or knockdown of Pde10a ameliorates the deficits observed in the heterozygous cKO mice. Collectively, our results suggest that MIR137 plays essential roles in postnatal neurodevelopment and that dysregulation of miR-137 potentially contributes to neuropsychiatric disorders in humans. Partial loss of psychiatric risk geneMir137 in mice causes repetitive behavior and impairs sociability and learning via increased Pde10a.